Nature Harmony and Local Wisdom: Exploring Tri Hita Karana and Traditional Ecological Knowledge of the Bali Aga Community in Environmental Protection - Qodim, Husnul (UIN Sunan Gunung Djati Bandung, 2023)
Environmental pollution has evolved into a global issue that affects all humans can feel. The most frequent cause is a massive land conversion that neglects the negative effects on the surrounding environment. The Bali Aga indigenous people in Trunyan and Tenganan villages have optimism about preventing a global ecological crisis by maintaining their customary forests. This study examines how the Bali Aga Indigenous people in Trunyan and Tenganan villages maintain their traditional ecological knowledge (TEK), their views on life, and how social institutions impact local wisdom, practices, and unique knowledge. Qualitative research methods—observation, in-depth interviews, and literature reviews—tracked and processed data. The research discovered a belief in Tri Hita Karana, prioritizing human balance with God and nature. The presence of binding customary law (Awig-awig) demonstrates the belief of the Bali Aga community in managing the forest and preserving its environment. The Awig-awig customary law has been implemented in both villages through diverse natural resource management techniques. It is further supported by their knowledge of the various plant species and their responsibilities in maintaining the ecosystem. Amid a global ecological crisis, the findings indicate that the Awig-awig or customary law plays a significant role in preserving the environment.